PENGEMBANGAN INDUSTRI KECIL (Studi Kasus Industri Bordir Kecamatan Sedan Kabupaten Rembang) - Tahwin, Muhammad (STIE YPPI Rembang, 2012)
Developing of small scale industry depends not only on the government policies but also the industrialist, it is the ability of the industrialist to compete their products (quality and quantity). So, the industrialist of the small scale industry have to follow the concrete steps to endure the existence of their business. One of the small and intermediate scale industry is Brodir Industry. Brodir industry has special characteristic, because it is the Indonesian culture which always exists consistency. Brodir belongs to consumerâs goods. It is shopping goods that belong to heterogeneous shopping goods, because the characteristic is more important than price aspect for the consumers. In other words, the consumers have different perceptions about the qualities and attributes. So, developing of Brodir craftsmen have to considers the relevancy between the craftsmen needs and the program carried out.Â Key Words: Craftsmen, Developing.